The Effect of Aromayoga on Body Weight of Contraceptive Injection Acceptors Experiencing Side Effects - Riris Sitorus; Grace Erlyn Damayanti Sihotang; Resha Astari; Eva Solina Br. Barus (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The three-month injectable contraceptive remains a popular hormonal method owing to its convenience and efficacy. Nevertheless, weight gain is a common adverse effect that often prompts discontinuation. Aromayoga—a therapeutic combination of aromatherapy and yoga—has emerged as a potential non-pharmacological strategy to mitigate this problem by restoring hormonal balance, relieving stress, and improving metabolic activity. Objective: This study sought to examine the impact of aromayoga on body weight among women using the three-month injectable contraceptive who experienced weight gain as a side effect. Methods: A quasi-experimental design employing a pretest–posttest control group approach was implemented. The study involved 30 women of reproductive age using the three-month injectable contraceptive, equally divided into an intervention group (n = 15) and a control group (n = 15). The aromayoga sessions were administered over a four-week period, three times weekly, with each session lasting 30 minutes. Statistical analyses were performed using paired-sample and independent t-tests.Results: The intervention group demonstrated a significant reduction in body weight with a mean decrease of 1.5 kg (p = 0.002), whereas the control group exhibited a mean weight increase of 0.3 kg (p = 0.084). Independent t-test analysis revealed a statistically significant difference between the two groups following the intervention (p = 0.015). Conclusions: The findings indicate that aromayoga is an effective non-pharmacological intervention for reducing weight gain among users of the three-month injectable contraceptive. Incorporating aromayoga into community health programs could promote user comfort and support the continued use of contraceptive methods.